2017
DOI: 10.7554/elife.25094
|View full text |Cite
|
Sign up to set email alerts
|

Dual role for Jumu in the control of hematopoietic progenitors in the Drosophila lymph gland

Abstract: The Drosophila lymph gland is a hematopoietic organ in which the maintenance of hematopoietic progenitor cell fate relies on intrinsic factors and extensive interaction with cells within a microenvironment. The posterior signaling center (PSC) is required for maintaining the balance between progenitors and their differentiation into mature hemocytes. Moreover, some factors from the progenitors cell-autonomously control blood cell differentiation. Here, we show that Jumeau (Jumu), a member of the forkhead (Fkh)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…Immunostaining against the heparan sulfate proteoglycan (HSPG) Dally-like protein (Dlp), which was described as a PSC marker (Pennetier et al, 2012) (see also Figure S2A), revealed that it is expressed at high levels in the posterior lobes and at very low levels in the MZ of the anterior lobes ( Figure 2D). Consistent with the idea that its expression is activated by Col (Hao and Jin, 2017), Dlp displayed an antero-posterior gradient of expression similar to that of col ( Figure 2D), with particularly strong levels in the tertiary lobes. RNA in situ hybridization against Dystroglycan (Dg), which encodes a cell surface receptor for the extracellular matrix, showed that it is strongly expressed throughout the posterior lobes and at lower level in the MZ of the anterior lobes ( Figure 2E).…”
Section: Anterior and Posterior Lobes Of The Larval Lymph Gland Diffesupporting
confidence: 85%
See 1 more Smart Citation
“…Immunostaining against the heparan sulfate proteoglycan (HSPG) Dally-like protein (Dlp), which was described as a PSC marker (Pennetier et al, 2012) (see also Figure S2A), revealed that it is expressed at high levels in the posterior lobes and at very low levels in the MZ of the anterior lobes ( Figure 2D). Consistent with the idea that its expression is activated by Col (Hao and Jin, 2017), Dlp displayed an antero-posterior gradient of expression similar to that of col ( Figure 2D), with particularly strong levels in the tertiary lobes. RNA in situ hybridization against Dystroglycan (Dg), which encodes a cell surface receptor for the extracellular matrix, showed that it is strongly expressed throughout the posterior lobes and at lower level in the MZ of the anterior lobes ( Figure 2E).…”
Section: Anterior and Posterior Lobes Of The Larval Lymph Gland Diffesupporting
confidence: 85%
“…The general view is that these lobes essentially harbor progenitors as initially suggested by the higher expression of DE-cadherin and the lack of expression of mature blood cell markers (Jung et al, 2005). Yet only few studies on progenitor differentiation in the primary lobe report on phenotypes in the secondary lobes (Owusu-Ansah and , Dragojlovic-Munther and Martinez-Agosto, 2013, Khadilkar et al, 2017b, Hao and Jin, 2017, Zhang and Cadigan, 2017, Kulkarni et al, 2011, Benmimoun et al, 2015. These studies revealed that posterior lobes could also differentiate in genetic contexts where there is extensive premature differentiation in primary lobes, however a thorough analysis of the posterior LG lobes is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The three genes dome, hedgehog and Antennapedia, which positively regulate hematopoiesis in the lymph gland [48], were reduced in circulating plasmatocytes compared to whole larvae, with FCs of -5.3, -173.9 and -2903.3, respectively. Similarly, genes that promote pro-hemocyte maturation in the lymph gland, such as jumu, pyramus, thisbe and heartless were also down-regulated in hemocyte samples (with FCs of -2.2, -31.9, -1151.8 and -1655.5, respectively) [49,50]. The gene encoding the transcription factor collier (knot) that contributes to the lymph gland posterior signaling center [51] was not enriched in plasmatocytes.…”
Section: Plos Onementioning
confidence: 99%
“…A previous study suggested that activation of the Toll pathway in hemocytes or fat body can induce lamellocyte formation [ 47 ]. Moreover, in a recent study, we demonstrated that loss of jumu in the entire lymph gland leads to the generation of lamellocytes through activation of Dif [ 34 ]. Thus, we next questioned whether the generation of lamellocytes in the circulating hemocytes of jumu GE27806 /Df(3R)Exel6157 was related to the Toll pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, our previous studies have shown that Jumu is also expressed in hemocytes and fat body, involved in proper bacterial phagocytosis and resistance in adult flies, and overexpression of jumu both in the fat body and hemocytes induces melanotic nodules by activating Toll signaling [ 32 , 33 ]. Our recent study showed that Jumu plays crucial roles during Drosophila lymph gland hematopoiesis [ 34 ].…”
Section: Introductionmentioning
confidence: 99%